Majlis Amanah Rakyat: a study on the deferred payment among MARA borrowers in Ranau, Kota Kinabalu / Rita Aulia Anwar - Anwar, Rita Aulia (2006)
This study was conducted in order to identify the deferred payment among MARA borrowers in Ranau, Kota Kinabalu. The study was merely focused on the current borrowers who have problems in repaying the Business Financing Scheme loan. A descriptive research approach has been chosen to study the problems faced by the MARA borrowers' especially borrowers who were specifically living in the Ranau district. This research approach was used as the researcher believed that it was the most appropriate to analyze the borrowers problems in paying back their loan under the scheme. In short, this research approach was used as it would explain an accurate description of the variables in the research questions that would be extremely support by later findings and analyses. The study revealed that there were only one hundred and thirty (130) respondents have been defaulted in their monthly loan repayment. This circumstance has become a big problem to MARA as it increased the number of deferred payment in the business loan. Therefore, collection of primary data was used based on personal interview where the respondents gave the answer according to the structured questions read out from the questionnaire form by the interviewer. In conjunction with this, collection of secondary data was also being carried out to support all primary data through literature review from several sources. Towards to the end of this study, the comprehensive recommendations have been established to reduce the deferred payment among current borrowers and at the same time improve the quality of services towards future borrowers.